THE UNSUCCESSFUL POVERTY REDUCTION STRATEGIES IN INDONESIA AND THE ALTERNATIVES SOLUTIONS (THE STUDY ON BLT AND JAMKESMAS) - Iriani, Dewi; Mahendra, Wahyu (UI Scholars Hub, 2014)
Indonesia as the 16th largest economy in the world, the 4th in Asia-after China, Japan and India as well as Southeast Asia’s largest-has the potential to be the seventh biggest by 2030, due to the increasing economic. Indonesia also has many potential natural resources that can be utilized to support development in order to increase the nation welfare. However, the number of poor people still has not been significantly reduced, reaching 28.07 million or 11.37% of the total population in 2013. The Government has tried to reduce poverty with some programs such as BLT (Bantuan Langsung Tunai/Direct Cash Assistance) and Jamkesmas (Jaminan Kesehatan Masyarakat/ Community Health Protection Scheme). However, the programs are considered not effective and do not make poor people become financially independent. Ironically, in inadequate evaluation, the Government continues to runs the programs. By using a qualitative approach, researchers will provide policy alternatives that can be implemented by Government.